Perlukah Tata Kelola Pengelolaan Dana Kemahasiswaan Dilakukan? - Ireina Thesa Shaula; Paramita Budirahayu; Ika Kristianti (Perspektif Akuntansi, 2022)
The phenomenon of the normalization student fund fraud at the Student Institution Faculty shown indications of fraudulent practices in the Student Institution. This study aims to learn how efficient the implementation of Good University Governance (GUG) at Faculty X, YZ University is in preventing student fund fraud. This study used a qualitative descriptive method with data collection techniques carried out by means of interviews and distributing questionnaires to the faculty legislature, faculty executive board, and faculty units. The stages in this research are divided into three parts, namely data reduction, data presentation, and drawing conclusions. The results of the study show that the Good Government University (GUG) principle that has been carried out by the Student Institution of Faculty X, YZ University is running quite well, but still needs to be improved to maximize student fund management. It is hoped that this research will bring benefits to the Student Institution of Faculty X, YZ University in assessing the risk of fraud and the controls needed in managing student funds.